2010
DOI: 10.1016/j.fertnstert.2010.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants, Oxyrase, and mitochondrial uncoupler 2,4-dinitrophenol improved postthaw survival of rhesus monkey sperm from ejaculates with low cryosurvival

Abstract: Various antioxidant strategies such as supplementation of antioxidants, limiting oxygen concentration with Oxyrase, and reducing reactive oxygen species (ROS) through mild mitochondrial uncoupling had significant beneficial effects on sperm cryopreservation from rhesus monkeys with low cryoresistant ejaculates. Individuals or species that have higher sensitivity to cryodamage may derive the most benefit from these treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Opening of mPTP is known to be induced during oxidative stress and ROS-mediated alterations to mPTP regulators and components were suggested to be responsible for this. Indeed, it was found that the mild uncoupling agent 2,4-dinitrophenol, which normally reduces ROS, improved motility in sperm with low cryopreservability [76] while the antioxidant, monothioglycerol was found to reduce mitochondria ROS as well as increase fertility and the percentage of cells with the ability to undergo acrosome reaction [41]. ROS-mediated mitochondrial permeabilization involved oxidative attack on the protein thiol groups on the mitochondrial membrane.…”
Section: Cryopreservation and Ros Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opening of mPTP is known to be induced during oxidative stress and ROS-mediated alterations to mPTP regulators and components were suggested to be responsible for this. Indeed, it was found that the mild uncoupling agent 2,4-dinitrophenol, which normally reduces ROS, improved motility in sperm with low cryopreservability [76] while the antioxidant, monothioglycerol was found to reduce mitochondria ROS as well as increase fertility and the percentage of cells with the ability to undergo acrosome reaction [41]. ROS-mediated mitochondrial permeabilization involved oxidative attack on the protein thiol groups on the mitochondrial membrane.…”
Section: Cryopreservation and Ros Productionmentioning
confidence: 99%
“…In one example, Dong et al reported that the beneficial effects of SOD administration were only seen in sperm with low post-thaw survivability [76]. This is also observed for other antioxidants namely coenzyme Q [218], resveratrol [219], zinc sulfate [220], ascorbic acid [150], catalase [76] and 2,4-dinitrophenol [76]. These studies concluded that the effectiveness of antioxidants was dependent on sperm quality.…”
Section: Effectiveness Of Antioxidants In Preventing Cryoinjury: Lessmentioning
confidence: 99%
“…It is known that high鈥怰OS levels can damage proteins, lipids, DNA, and membrane system . SOD, as well as catalase, peroxidase, glutathione peroxidase, glutathione reductase, and non鈥恊nzymatic antioxidants together form a defense system to reduce the risk of ROS damage . SODs have recently found applications in the pharmaceutical and cosmetic industries, food, agricultural, and chemical industries .…”
Section: Introductionmentioning
confidence: 99%
“…With the addition of glycerol, LDL at lower concentrations (2%-6%) yielded similar post-thaw motility (46%-54%) and AMI (28)(29)(30)(31)(32)(33)(34) as that of 8% LDL (53%66% for motility and 3368 for AMI) or 10% LDL (53%69% for motility and 36610 for AMI).…”
Section: Evaluation Of Ldl In Combination With Glycerolmentioning
confidence: 88%